An Optimization Model for Risk Minimization in Stock Portfolio Selection - Alkhaledi, Khaled; Dalalah, Doraid (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
Stock portfolio selection is a challenging task for investors due to its multidimensional aspects. Investors always aim to maximize the expected return on their investments while maintaining a reasonable level of risk. Therefore, the appropriate choice of stocks is vital to achieving the desired return with minimal risk in financial markets. The objective of this study is to help answer the question of how to invest a specific amount of money across a range of assets in the safest and most effective way to achieve the maximum desired return with the minimum risk. A linear optimization model was developed to minimize overall investment risk, subject to realistic constraints such as the expected total return and investment ratios among different asset categories. To validate the model, a group of well-established securities was selected from various industries in the United Arab Emirates. Historical data spanning five years were collected for each stock category. In this study, stocks were grouped into five categories: construction, transportation, logistics, telecommunications, and banking. The optimization model was solved using Excel Solver with the simplex method. The results showed that the investment proportions satisfied all constraints, the objective function was optimized, and the best stock portfolio was determined. The model can help investors identify optimal portfolio allocations that achieve a target return while minimizing risk.